2022
DOI: 10.1097/ee9.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of community deaths during the catastrophic 2021 heat dome

Abstract: Background: British Columbia, Canada, was impacted by a record-setting heat dome in early summer 2021. Most households in greater Vancouver do not have air conditioning, and there was a 440% increase in community deaths during the event. Readily available data were analyzed to inform modifications to the public health response during subsequent events in summer 2021 and to guide further research. Methods: The 434 community deaths from 27 June through 02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 31 publications
0
84
0
3
Order By: Relevance
“…In BC, Alberta and Saskatchewan, periods early in the pandemic and at the end of the reported period saw excess mortality rates far higher than those for COVID-19. In particular, BC saw a notable, sustained divergence after the spike in deaths related to the 2021 “heat dome.” 7 …”
Section: What Do Publicly Available Data Show?mentioning
confidence: 99%
See 1 more Smart Citation
“…In BC, Alberta and Saskatchewan, periods early in the pandemic and at the end of the reported period saw excess mortality rates far higher than those for COVID-19. In particular, BC saw a notable, sustained divergence after the spike in deaths related to the 2021 “heat dome.” 7 …”
Section: What Do Publicly Available Data Show?mentioning
confidence: 99%
“…Some provinces, especially BC, had an unexpected heat dome in June and July 2021, which, as noted, was associated with a spike in deaths. Human Rights Watch concluded that an inadequate policy response contributed to heat-related deaths in BC, 10 and that these deaths were highly associated with social and material deprivation, 7 which may have been related to the COVID-19 pandemic. Pandemic policies and border shutdowns likely also contributed to an unsafe drug supply, more people using alone and other social factors that contributed to higher rates of opioid-related deaths.…”
Section: What Is the Meaning Of The Different Mortality Patterns Acro...mentioning
confidence: 99%
“…These metrics, hence, define existential risks, because they indicate certain thresholds beyond which risks become existential, according to scientific or societal standards. Recent examples where extraordinary high magnitudes were reached are the devastating 2021 floods in western Europe with statistically extremely high rainfall intensities and flood discharges (Fekete and Sandholz 2021 ), or the heatwave (heatdome) that struck the northwestern USA and southwestern Canada in 2021 with extremely high temperatures close to 50°C (Henderson et al 2022 ). Other types of metrics for magnitude relate to the number of affected people, the geographic or administrative area affected (e.g., from provincial to national scale), the area of arable land, or the number of systems or sectors affected (e.g., food and energy production systems) (IPCC 2014 , 2018 , 2019b ; Hirabayashi et al 2021 ).…”
Section: Elements and Dimensions Of The Existential Risk Space Of Cli...mentioning
confidence: 99%
“…En Colombie-Britannique, en Alberta et en Saskatchewan, le début de la pandémie et la fin de la période étudiée ont été associés à des taux de surmortalité beaucoup plus élevés que les taux de mortalité liée à la COVID-19. La Colombie-Britannique, en particulier, a connu un important écart soutenu après le pic de mortalité liée au « dôme de chaleur », en 2021 7 .…”
Section: Que Révèlent Les Données Publiques?unclassified
“…Certaines provinces, surtout la Colombie-Britannique, ont connu un dôme de chaleur inattendu en juin et juillet 2021 qui a été associé à un pic de mortalité. Human Rights Watch a conclu qu’une réponse inadéquate des pouvoirs publics avait contribué aux décès liés à la chaleur en Colombie-Britannique 10 et que ces décès étaient étroitement liés à des difficultés sociales et matérielles 7 ayant peut-être été associées à la pandémie de COVID-19. Les politiques et les fermetures de frontières adoptées en raison de la pandémie ont aussi probablement favorisé la mise en circulation de drogues dangereuses, la consommation en solitaire et d’autres facteurs sociaux ayant contribué à l’augmentation des taux de décès par surdose d’opioïdes 11 .…”
Section: Que Signifient Ces Différentes Courbes De Mortalité Entre Le...unclassified